Elevated Plasma Soluble Triggering Receptor Expressed on Myeloid Cells-1 Level in Patients with Acute Coronary Syndrome (ACS): A Biomarker of Disease Severity and Outcome - Shachaf Shiber; Vitaly Kliminski; Katia Orvin; Iftach Sagy; Mordehay Vaturi; Ran Kornowski; Michael Drescher; Yair Molad (Mediators of Inflammation)
Background and Aims. Plasma levels of soluble triggering receptor expressed on myeloid cells (sTREM-1) reflect innate immune cell activation. We sought to evaluate sTREM-1 levels in patients with acute coronary syndrome (ACS) and their predictive value for disease severity and outcome. Methods. Plasma sTREM-1 levels were prospectively measured by ELISA in 121 consecutive patients with new-onset (≤24 h) chest pain at arrival to the emergency department (ED) and 73 healthy controls. Secondary endpoints were the association of plasma levels of sTREM-1 with day 30 and month 6 major adverse cardiovascular events (MACE) defined as death, ACS, stroke, and need for coronary revascularization, as well as with CAD severity. The primary endpoint of the study was the association of plasma sTREM-1 level at the time of admission to the ED with a diagnosis of ACS at day 30. Results. Fifty-nine patients (48.7%) were diagnosed with ACS and 62 (51.3%) with nonspecific chest pain (NSCP). Median plasma sTREM-1 level at admission was significantly higher in the ACS group than the NSCP group and the control group (539.4±330.3 pg/ml vs. 432.5±196.4 pg/ml vs. 230.1±85.5 pg/ml, respectively; P<0.001) and positively correlated with the number of stenosed/occluded coronary arteries on angiography (P<0.001). On logistic regression analysis, higher sTREM-1 levels predicted definite ACS vs. NSCP determined on day 30 (OR 1.29, 95% CI 1.07-1.54, P=0.01) as well as with recurrent ACS (P=0.04) and stroke (P=0.02) at 6 months. Conclusions. Plasma sTREM-1 levels are significantly elevated in patients with ACS and might serve as a biomarker differentiating ACS from NSCP in the ED as well as an inflammatory biomarker for coronary artery disease severity and outcome.